Effect of high hydrostatic pressure (HHP) on crystal structure of palm stearin emulsions. (August 2017) - Sevdin, Sezen; Yucel, Umut; Alpas, Hami
Abstract: High hydrostatic pressure (HHP) treatment was used to control the crystallization behavior of solid lipid nanoparticles stabilized with sodium caseinate (SC) and soy lecithin Phospholipon 80H (80H). Samples were pressurized at 100 and 500 MPa, at 10, 20 and 40 °C for 15 min. The stability of emulsions was analyzed by visual observation for gelation, and the change in the droplet size distribution using light scattering measurements after HHP treatment and storage for 28 days at 4 °C. The crystal micro-structure (i.e., solid lipid content and crystal morphology) were evaluated from differential scanning calorimetry (DSC) thermograms for melting enthalpies and temperatures. Initial droplet size (0.199 μm for 80H and 0.182 μm for SC) was not affected significantly (p > 0.05) either by HHP processing or storage. DSC results showed that pressure has a significant effect (p < 0.05) on the crystal polymorphs contents. Change in polymorphic content due to HHP treatment was approximately 50% at the first day of storage for all samples. Storage time was also found to be significantly effective (p < 0.05) on polymorphic structure and the change in polymorphic content was approximately 46% throughout the storage period. It was shown that HHP treatment can be used to control the crystal morphology of crystalline lipid droplets, which can serve as potential encapsulation systems for bioactive molecules. Graphical abstract: Highlights: HHP treatment affected the crystalline structure of emulsions. β crystal content can be increased up to 50% with HHP treatment. Polymorphic transitions during storage can be minimized by HHP. HHP does not cause any change in particle size and stability.